STRATEGI GURU TAHFIZ DALAM MENINGKATKAN HAFALAN AL-QURAN PESERTA DIDIK SEKOLAH DASAR ISLAM TERPADU CAHAYA MADANI KECAMATAN LUBUK SIKAPING - Tolani, Suri; Ritonga, Mahyudin; Rahmi, Rahmi (Tarbiyah al-Awlad, 2021)
The Covid-19 period is classified as a difficult situation for various parties in succeeding activities in accordance with the planned objectives, as well as in learning especially for elementary school level. Therefore, this study is designed to reveal the strategy of teachers tahfiz SD IT Cahaya Madani Lubuk Sikaping in improving the memorization of students in the Era of Covid-19. In line with the above objectives, the method used in this study is qualitative descriptive with phenomenological approach, the data source used is tahfiz teacher and student at SD IT Cahaya Madani Lubuk Sikaping. The data is collected by observation techniques, interviews and documentation studies. The results showed that the teacher's strategy in teaching tahfiz during Covid-19 was implemented through the application of sima'i method using voice note feature on whatsapp application, application of memorization method using video recording, and application of home-based interactive learning strategy (Piber). The ability to memorize the Quran of STUDENTS of SD IT Cahaya Madani during the Covid-19 pandemic showed good results. Students are able to complete memorization and increase the number of memorizations according to the target set, and able to maintain the quality of memorization amid the limitations of learning. Supporting factors in the implementation of tahfiz learning during the Covid-19 period at SD IT Cahaya Madani include teacher competence, availability of gadgets/ smartphones / gadgets, and internal cooperation of the school. While the factors that become obstacles to the implementation of learning related to the limitations of the allocation of learning time, differences in student abilities, student learning motivation, learning places, and internet networks.